Analysis Of Musculoskeletal Drivers Literature: A Comprehensive Review Of Scientific Publications - Setyo Nugroho, Bayu Yoni; Pramitasari, Ratih; Treesak, Chalobon; Ximenes, Adriano (Disease Prevention and Public Health Journal, 2025)
Background:Musculoskeletal disorders among professional drivers represent a significant occupational health challenge, with prevalence rates of 78.6% globally, causing physical discomfort, reduced performance, and increased workplace injury risks. The objective of this study is to provide a comprehensive overview of MSD research development and guide future research directions based on quantitative analysis of scientific publications. Method: A comprehensive bibliometric analysis was conducted using Web of Science database data from August 10, 2025. The search included open access English articles on "Back pain" and "Transportation" using VOSviewer and R-Bibliometrix tools to visualize inter-literature connections and research evolution. Results: Dominance of “Public Environmental” category is well quantified of 112 documents revealed. The United Kingdom, USA, and Australia led research contributions with strong international collaborations. Four thematic clusters emerged: Motor Themes (exposure, prevention, ergonomics), Basic Themes (driving safety, automation), Niche Themes (human factors), and Emerging Themes (occupational health, systems thinking). Key focus areas included whole-body vibration, low-back pain, ergonomic interventions, and health prevention strategies. Conclusions: Significant gaps exist between assessment studies and comprehensive intervention development in driver musculoskeletal health research. Despite extensive research foundations in developed countries, intervention studies remain limited, particularly in developing nations. The analysis emphasizes the need for cost-effective ergonomic interventions, longitudinal studies, and direct measurement techniques to address the complex interplay of work procedures, environment, and equipment in musculoskeletal disorder development among professional drivers.